Improving the resilience of urban transportation to natural disasters: the case of Changchun, China - Ziyang Wan; Qiuling Lang; Yichen Zhang; Jiquan Zhang; Yanan Chen; Gexu Liu; Huanan Liu (Scientific Reports)
Abstract This study quantitatively assesses the resilience of the urban transport system in Changchun under extreme climatic conditions, focusing on the impacts of natural disasters such as snowstorms, strong winds and extreme low temperatures on the transport system. The vulnerability, exposure, and emergency recovery capacity of the transport system in Changchun were analyzed by constructing a comprehensive assessment framework combining multi-criteria decision analysis (MCDM) and geographic information system (GIS). Based on the meteorological and traffic data of Changchun City in the past 10 years, key indicators such as traffic network density, emergency resource distribution, traffic flow, and extreme weather frequency were selected in this study. The weights were calculated by the improved hierarchical analysis method (AHP) and entropy weighting method, and finally the traffic resilience of Changchun city was quantitatively analyzed. The results show that there are significant spatial differences in the toughness of the transport system in Changchun, of which 38.6% of the areas have very low toughness and are concentrated in the urban fringe and urban–rural areas; 25.3% of the areas are at a medium level of toughness; and 5.4% of the areas show high toughness and are mainly located in the city center and important transport hubs. This study proposes transport resilience enhancement strategies for different areas of Changchun, with special recommendations for strengthening infrastructure development, optimizing traffic management and emergency response capacity in low resilience areas. The results of this study provide a scientific basis for Changchun to cope with future extreme climate challenges, and a reference framework for other cities with similar climatic conditions.